2019
DOI: 10.1115/1.4043889
|View full text |Cite
|
Sign up to set email alerts
|

Mode I and II Interlaminar Fracture in Laminated Composites: A Size Effect Study

Abstract: This work investigates the mode I and II interlaminar fracturing behavior of laminated composites and the related size effects. Fracture tests on geometrically scaled Double Cantilever Beam (DCB) and End Notch Flexure (ENF) specimens were conducted to understand the nonlinear effects of the cohesive stresses in the Fracture Process Zone (FPZ). The results show a significant difference between the mode I and mode II fracturing behaviors. It is shown that, while the strength of the DCB specimens scales according… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…For higher a wt.% of HMWCNTs, discontinuous cracking, microcrack deflection, and pinning, or fiber/tow bridging of the crack, lead to highly nonlinear cohesive stresses, and hence the improved crack propagation resistance. Several researchers [ 73 , 74 , 75 ] have confirmed this underlying principle in the fracture of composite laminates. However, to capture and quantify the nonlinear stresses close to the crack tip, the introduction of a characteristic length scale associated with the size of the FPZ is necessary [ 73 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 83%
“…For higher a wt.% of HMWCNTs, discontinuous cracking, microcrack deflection, and pinning, or fiber/tow bridging of the crack, lead to highly nonlinear cohesive stresses, and hence the improved crack propagation resistance. Several researchers [ 73 , 74 , 75 ] have confirmed this underlying principle in the fracture of composite laminates. However, to capture and quantify the nonlinear stresses close to the crack tip, the introduction of a characteristic length scale associated with the size of the FPZ is necessary [ 73 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 83%
“…This is typically the case of structures featuring open and filled holes, sharp notches and other stress raisers. In such a case, a quasibrittle fracture mechanics framework should be preferred over a stress-based failure criterion [53][54][55][56][57]. All the required material properties such as longitudinal and transverse elastic moduli E 1 and E 2 , shear modulus G 12 , Poisson's ratio ν 12 , and the ply strengths: σ f 1t , σ f 1c , which are tensile and compressive strengths in the fiber direction, σ f 2t , σ f 2c , which are tensile and compressive strengths perpendicular to the fiber directions, and τ f 12 , that is shear strength are respectively assigned and tabulated in Table 1.…”
Section: Problem Setupmentioning
confidence: 99%
“…The size effect of the laboratory scale test is an important issue in these cases. Salviato et al [ 29 ] analyzed Bažant’s size effect law to take into account the nonlinear effects of the fracture process zone on DCB and ENF delamination testing. They concluded that applying this law the fracture behavior is properly determined.…”
Section: Introductionmentioning
confidence: 99%